(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
The integration of advanced pedagogical technologies in the training of philology students is essential for developing their linguistic proficiency, critical thinking, and teaching skills. This paper examines the various pedagogical technologies employed in philology education, their effectiveness, and their impact on students’ learning outcomes. The study emphasizes the significance of interactive and digital tools in enhancing the educational experience and preparing students for the evolving demands of the linguistic and educational fields